A protein in urine associated with muscle disease and muscle damage. Issue 6281 (20th June 1981) - Frearson, N; Taylor, R D; Perry, S V
Abstract : Analysis of the protein composition of human urine by high-resolution two-dimensional electrophoresis showed that several features are associated with neuromuscular diseases, the best defined being the appearance in the urine of a small amount of a protein that migrates on the electropherogram as a characteristic spot (spot C). This spot consists of a protein of apparent molecular weight 26 000 and isoelectric point 5.3. The spot was usually present in the urine of patients suffering from diseases in which the musculature was directly affected but was rarely found in other patients and normal subjects. The protein responsible for spot C appears to be an index of muscle damage caused by a number of conditions. Attempts are being made to isolate enough of the protein to permit its identification.